Analysis of color stability and degree of conversion of different types of resin composites - Mylena Proença COSTA; Juliana Carvalho JACOMINE; Victor MOSQUIM; Daniella Cristo SANTIN; Giovanna Speranza ZABEU; Maria Angélica Silvério AGULHARI; Rafael Francisco Lia MONDELLI; Heitor Marques HONÓRIO; Linda WANG (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Resin composites containing surface pre-reacted glass (S-PRG) have been introduced to reduce demineralization and improve remineralization of the tooth structure. However, water diffusion within the material is necessary for its action, which can impair its overall physicomechanical properties over time, including color stability. This study aimed to evaluate the color stability and related degree of conversion (DC) of four resin composites. Discs (6 x 4 mm, n = 5/group) of microhybrid (MH), nanofilled (NF), nanohybrid (NH), and S-PRG-based nanohybrid (S-PRG-NH) composites with two opacities (A2/A2E and A2O/A2D) were prepared. Color (CIELab and CIEDE2000) was evaluated with a spectrophotometer after aging in grape juice (2 x 10 min/10mL/7days). The DC was analyzed by using Fourier transform infrared spectroscopy before and after light-curing. Data were statistically analyzed by using two-way analysis of variance and post-hoc least significant difference tests (p<0.05). In the color stability analysis, the interaction between filler type and opacity was significant (CIELab, p = 0.0015; CIEDE2000, p = 0.0026). NH presented the highest color stability, which did not differ from that of MH. The greatest color alteration was observed for S-PRG-NH. S-PRG fillers also influenced DC (p < 0.05). The nanohybrid resin composite presented favorable overall performance, which is likely related to its more stable organic content. Notwithstanding the benefits of using S-PRG-based nanohybrid resins, mostly in aesthetic procedures, professionals should consider the susceptibility of such resins to color alteration, probably due to the water-based bioactive mechanism of action.